Aspirin for Primary Prevention of Cardiovascular Events in the Elderly: Current Status and Future Directions - Ward, Stephanie A.; Demos, Lisa; Workman, Barbara; McNeil, John J. (Drugs & aging, 2012)
The role of aspirin in the secondary prevention of occlusive cardiovascular events has now been well established. Given this, aspirin in primary prevention has been the focus of several large trials and subsequent meta-analyses over the past 3 decades, and yet the issue remains controversial. Recent studies in populations with high baseline risk — such as diabetics and those with asymptomatic peripheral arterial disease — have not found the expected benefits of aspirin on cardiovascular endpoints, which contrasts with earlier studies that reported a reduced relative risk for outcomes such as myocardial infarction and ischaemic stroke, but not for mortality. Furthermore, in healthy populations, the absolute risk reduction conferred by aspirin is small and needs to be balanced against the risk of a major haemorrhage. Older adults have a higher risk for cardiovascular events and therefore might represent the group in which aspirin for primary prevention could deliver the greatest absolute benefit, yet at the same time, the elderly bear an increased vulnerability to major haemorrhage, including haemorrhagic stroke. It is also not known whether older adults experience the same risk reduction from aspirin as middle-aged individuals. The current evidence base does not sufficiently clarify whether aspirin for primary prevention confers a meaningful net benefit in the elderly.